Pests on a platter - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
The Ento Doc bi-lingual (French and English) CD-ROM is user-friendly and consists of 92 factsheets about pests and beneficials with hypertext links and descriptions of pests, their biology, the damage they cause and control techniques